Development of entrepreneurial activity in the Czech Republic over the years 2005-2017 - Ondřej Dvouletý (Journal of Open Innovation: Technology, Market, and Complexity, 2019)
Although there is a rich debate about entrepreneurship and its impact on economic development, much less is known about the actual levels of entrepreneurial activity. The main aim of the article is, thus, to map the level of entrepreneurial activity in the Czech Republic, its structure, and development during the years 2005-2017. The study is based on the secondary data obtained from national structural business statistics, the Global Entrepreneurship Monitor, and the Labour Force Survey. The average rate of entrepreneurial activity in the Czech Republic was 15.2% of the economically active population aged 15-64 years during the analysed period. The activity is dominated by solo-self-employed workers (own-account workers). Job creators represent only 3.2% of the economically active population. Patterns and cohorts of entrepreneurs were identified regarding gender, age, and education. There were 2.5 times more self-employed males compared to females for the past years, and the proportion of job creators is also higher for males. The Czech job creators are on average older (mostly represented in age cohort 40-49 years) compared to solo-self-employed (mainly represented in age cohort 35-44 years) and they have obtained tertiary education to a larger extent. Classification and monitoring of the Czech entrepreneurial activity might serve as an overview for Czech policymakers and regional scholars. Especially from a job creation perspective, it might be very relevant to understand the characteristics of those individuals who employ other workers, aside from themselves. From an international perspective, this study might serve as an inspiration to shed more light on the national levels of entrepreneurship and self-employment.
Keywords: 650; classification of entrepreneurs; Czech Republic; entrepreneurial activity; labour force survey; measuring entrepreneurship; self-employment rate